The role of magnetic resonance imaging brain in estimating the burden of preventable and potentially curable epilepsy in developmentally normal children - Upadhyay, Jaya; Chaudhary, Prachi; Thora, S (Indian Journal of Child Health, 2018)
Background: Epilepsy is the most common neurological condition among children. Diagnosis of epilepsy is clinical, but to find the etiology we must depend on investigations such as electroencephalography (EEG) and magnetic resonance imaging (MRI) f the brain. EEG is more useful to diagnose genetic epilepsies, and MRI is more useful in structural causes. Objective: The objective of this study was to find the etiology of epilepsy prevalent in children of our region and to evaluate the role MRI brain in diagnosis. Methods: This was a survey-based study conducted at a tertiary care hospital in central India, between April 2015 and August 2016. A total of 108 developmentally normal children in the age group of 1 month to 14 years who presented with two or more unprovoked seizures 24 h apart or known case of epilepsy and on treatment admitted in the inpatient department for seizures were included in this study. The patients were classified based on detailed history, personal observation of seizures in some cases, thorough clinical examination, EEG recording, MRI findings, and other relevant investigations pertaining to the case, and the data were analyzed. Results: According to the ILAE 2010 classification, 12.9% of our patients had probable genetic epilepsy, 32.4% belonged to the structural metabolic group, and 54%, the largest proportion had an unknown cause. Of total 42 patients with abnormal MRI, 30 (71.42%) patient had underlying structural or metabolic abnormality, whereas 28.57% had a genetic cause. 10 patients had imaging results suggestive of neurocysticercosis, while 7 patients had mesial temporal sclerosis. Gliosis was seen in nine patients, tuberculoma was seen in four patients, and finding suggestive of infarcts was seen in six patients. Remaining patients had abnormalities including corpus callosal agenesis (1), cortical dysplasia (2), tuberous sclerosis (1), white matter disease (1), and hippocampal hyperintensities suggestive of encephalitis (1). Conclusion: MRI brain is the most important routinely available investigation and must be utilized. Neurocysticercosis is still the most common structural cause of epilepsy in children in our region.